(3CSGSjGJ GdEbJUGO GdfbOj hGdeUQaj (B/s - (3MTjT, YGOd CMeOs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2014)
(3jVe EQJHGW fTCI GdfbhO hJWhQ hXGFagG Hfeh GbJUGO GdeHGOdI hGdJWhQGJ GddGMbI HGdQCSeGdjI cfXGe GbJUGOj, CfhGY GdfbhO hhMOGJ GdfbO GdeJOGhd eY GdETGQI ddCLRGA GdebGHdI ddcJdI GdfbOjI, OhGYj JWhQ hSGFd hCOhGJ JShjI GdeOahYGJ hXghQ eG jYQa HGdfbhO GdEdcJQhfjI hGdLOd Mhd GdWHjYI GdfbOjI dgPg GdfbhO, bjeI GdfbhO hYdGbJgG HGdeSJhi GdYGe ddCSYGQ hGdYhGed GdhGVMI ddJbdHGJ GdfbOjI GdWGQFI Ydi gPg GdbjeI heG jfLe YfgG ef BKGQ, GdSjGSI GdfbOjI hGdCgOGa GdeJhNGI efgG aj eYGdLI GdJbdHGJ GdWGQFI Ydi bjeI GdfbhO, eGgjI hNUGFU GdfXGe GdfbOj hGfYcGSGJ GdChVGY GdEbJUGOjI Ydi GdfXe GdfbOjI GdSGFOI, GdHfhc ceDSSGJ fbOjI hJehjdjI, CSGSjGJ GdfTGW GdEFJeGfj ddHfhc hGdhXGFa GdCSGSjI ddhSWGA GdeGdjjf, GdHfhc GdJLGQjI, GdHfc GdeQcRjs
(3HHdjhZQGajG(B: (3U(B.333-338s
Keywords: (3GdEbJUGO GdeGdjs; (3GdHfhcs; (3GdfbhOs